Factors Affecting the Level of Key Audit Matters Disclosure: Evidence from Jordan - Ali Alduneibat, Khalid (Jordan Journal of Business Administration, 2024)
The current study aimed at investigating the level of disclosure of Key Audit Matters (KAMs) in the audit reports of Jordanian companies listed in the Amman Stock Exchange (ASE) as required by the International Standard on Auditing 701 (ISA 701). The study also aimed at examining the factors affecting the level of KAM disclosure. In order to accomplish the objectives of the current study, 324 annual audit reports from 2017 through 2019 of 108 companies are examined. Potential KAM issues are recognized through companies’ audit reports, while corporate characteristics are gathered from companies’ annual reports. Three major analytical methods are applied to analyze the defined model and the recruited data, including descriptive statistics, correlation and ordinary least squares (OLS) regression analysis. The results of the study demonstrate that the mean of KAM-disclosure level is 1.58, which is considered to be relatively low. Positive relationships are attested between the number of KAMs disclosed and the independent variables: size, leverage, indebtedness, auditors’ fees and big-four (audit firm size). However, the results suggest that there are negative relationships between the level of KAMs disclosed and two independent factors: profitability and modified opinions. Additionally, the results of the study revealed that accounts’ receivables and provisions represent the highest level of KAM reporting ratio. This study significantly contributes to the body of literature addressing the awareness of KAM-disclosure level and its determinant factors in Jordan. The study recommends that KAM disclosure in Jordan should receive more attention from preparers and users of financial statements.